PEO Coatings with Active Protection Based on In-Situ Formed LDH-Nanocontainers. Issue 2 (1st January 2017) - Serdechnova, M.; Mohedano, M.; Kuznetsov, B.; Mendis, C. L.; Starykevich, M.; Karpushenkov, S.; Tedim, J.; Ferreira, M. G. S.; Blawert, C.; Zheludkevich, M. L.
Abstract : In the present work, for the first time Zn-Al layered double hydroxide (LDH) nanocontainers were grown in-situ on the surface and in the pores of plasma electrolytic oxidation (PEO) layer and then loaded with a corrosion inhibitor to provide active protection. The developed LDH-based conversion process ensures partial sealing of the pores and provides an effective corrosion inhibition on demand leading to increased fault-tolerance and self-healing properties. The structure, morphology and composition of the LDH-sealed PEO coatings on 2024 aluminum alloy were investigated using SEM, TEM/FIB, XRD and GDOES. Electrochemical impedance spectroscopy and scanning vibrating electrode techniques show a remarkable increase in the corrosion resistance and fault tolerance when PEO coating is sealed with a LDH-inhibitor treatment.